Gestão pública de resíduos sólidos da construção civil em Aracaju : um desafio ambiental - Tavares, Denisia Araujo Chagas (2007)
Civil construction is one of the main sources of environmental degradation, being the biggest generating source of society s residues, as well as responsible for harmful residue deposits throughout the different stages of its productive process. In Brazil, until beginning of the 90 s, this sector did not attend to environmental questions, resulting in several environmental problems that were aggravated for the intense urbanization process during the second half of the last century, provoking an enormous demand for new housing construction. This thesis examines solid waste and residue management practices by civil construction companies located in Aracaju, based on research of interventions by governmental entities, company associations, recycling cooperatives, transporters of rubbish, and other entities in areas related with the environmental management of these residues. The data collection was from both primary and secondary sources. To attain primary data, questionnaires were applied to agents involved with the management of Construction and Demolition Wastes (CeDW) - managers of responsible public agencies, unionized professionals, "System S", cooperatives, transporting and consulting companies. The survey method for secondary data was based on bibliographical research of residue and waste evaluations already carried out by construction companies in Brazil and Aracaju. Although the majority of local constructors admit knowledge of the legislation that compels them to manage these residues, it has not, in fact, led to routine, proper practices by these companies. In Aracaju, the average amount of irregular residue and waste deposits by civil construction is 505 tons/day, with a total of 295 deposit sites. An important contributing factor explaining the lack of local interest in Construction and Demolition Wastes management is the absence of an Integrated Plan for the Management of Construction and Demolition Wastes, which could enforce implantation of an Area Overflow and Selection Plan and the identification of Waste Sites for Civil Construction. Moreover, governments have not stimulated the creation of new enterprises for the recycling of CeWD, which would be important since 75,9% of the CeWD of the haphazard and irregular dumping sites in Aracaju have great potential for re-utilization and/or recycling. The internalization of ambient external costs through government involvement must occur through a balanced combination of environmental policy instruments, such as direct regulation, economic and communication instruments. Because of the low degree of public intervention and of the negative environmental impacts caused by residues and wastes, the thesis argues for the creation of new specific public policies to oversee the reduction of generated wastes at the source, the reuse of leftover materials at constructions sites, policy incentives to stimulate recycling, disposal and treatment of wastes, and expanding the services related to residues in order to reduce degrading environment consequences.